Treści bibliologiczne na łamach „Łowca Polskiego” w latach 1989-2011 - Wańka, Danuta (Biblioteka Uniwersytecka w Poznaniu, 2012)
W artykule przedstawiono problematykę bibliologiczną w świetle 23 roczników „Łowca Polskiego” (1989–2011) ukazującego się od 1899 roku. Po krótkiej prezentacji dziejów i zawartości pisma opisano i zacytowano fragmenty tekstów o charakterze bibliologicznym. Niektóre z nich przytoczono ze szczegółami, traktując je jako materiały źródłowe, ważne dla badań nad kulturą książki.

The article discusses bibliological issues as presented in 25 annual (issues) publications of Łowiec Polski (between 1989 and 2011) published since 1899. Following a short presentation of the history and the core content of the periodical, the author discusses and cites sections of the texts that are of decidedly bibliological nature. Some of them are given in extensive excerpts and are treated as source material of importance for the research and the study on the culture of book.
The content related to the study of book as physical and cultural object in Łowiec Polski in the years 1989-2011
Keywords: Bibliofilstwo; Bibliophilia; czasopisma przyrodniczo-łowieckie; nature and hunting magazines (periodicals); Łowiec Polski; kolekcjonerstwo; collecting